Pengaruh Media Papan Baca terhadap Kemampuan Membaca Siswa Kelas 2 di SD Negeri 015 Kenangan Kabupaten Pasangkayu: The Influence of Reading Board Media on the Reading Ability of Grade 2 Students at SD Negeri 015 Kenangan, Pasangkayu Regency - L. Agung Kirana. D; Nurul Fitriah Aras; Sinta Satria Dewi Pendit; Zulnuraini Zulnuraini; Kasmawati Kasmawati (ITScience (Information Technology and Science), 2026)
This study aims to determine the effect of using reading boards on the reading ability of second-grade students at SD Negeri 015 Kenangan, Pasangkayu Regency. The study used a quantitative, pre-experimental design in the form of a one-group pretest-posttest. The research subjects were 10 students selected through saturated sampling. Data were collected through tests, observations, and documentation, then analyzed using descriptive and inferential statistics. The results showed an increase in students' reading ability after using the reading board media. The average pretest score of 53.20 increased to 77.30 in the posttest. The results of the normality test showed that the data were normally distributed, and the paired-samples t-test yielded a p-value <0.001 (<0.05), indicating a significant difference between the pretest and posttest. The N-Gain value of 0.52 is in the moderate category, while the effect size of 2.08 is in the very large category. The increase in reading ability is evident in letter recognition, syllable combination, pronunciation, and simple reading comprehension. These findings indicate that reading boards are effective in improving students' early reading skills because they provide a concrete, visual, and interactive learning experience, and can increase student motivation and engagement in the classroom. Therefore, reading boards can be used as an innovative learning alternative to improve the literacy skills of elementary school students.